Effect of salt stress on acid phosphatase activity and phosphorus content of Lycopersicon peruvianum L. under in vitro culture - F., Soltani Nezhad; A.A., Ehsanpour; S.M., Hosseini (Penerbit Universiti Kebangsaan Malaysia, 2011)
In this study, the effect of different concentrations of NaCl (0, 60, 90, 120 and 150 mM NaCl) on phosphorus content and acid phosphatase (APase) activity in Lycopersicon peruvianum L were investigated. Results indicated that phosphorus content was decreased and Apase activity was increased at 150 mM NaCl. With increasing salinity levels phosphorus content of roots decreased in all NaCl concentrations, but the Apase activity increased significantly with increasing salt concentrations. Salt stress did not change the relative chlorophyll content of leaves. It can be concluded that salt stress may induce APase activity accompanied by a low level of Pi.